PEMANFAATAN TUMBUHAN SEBAGAI SIMPLISIA OBAT TRADISIONAL DI DESA TRUNYAN - Sang Ketut Sudirga (Environmental Research Center (PPLH) of Udayana University)
Research on conservation and the use of plants as sources of traditional medicine wascarried out in Trunyan village. Objectives of this research are as follows: (1) To find outplant species used as traditional medicine; (2) Which parts of plants utilized for medicine; (3)Names of diseases which can be treated, and (4) What action has been taken by the villagersto conserve these plants. The research was carried out for two months within five banjar:Banjar Mukus, Puseh, Madia, Bunut, and Banjar Trunyan. Data were collected throughinterview, on site observation and literature review, and then they were qualitatively as wellas quantitatively analyzed and presented in tables.Results of this research showed that 90 species of plants were identified as materialfor traditional medicine in Trunyan village. Leaves were parts of plants which were usedmost (46.21%), and diseases which can be cured such as coughing, skin diseases, stomachdisorder, rheumatics, hard breathing, fever, and headache, the diseases of which aregenerally not fatal. From the conservation perspective, it was found that very littleproportion (10%) of this species which have been cultivated.